PENGARUH SUBSTITUSI ABU AMPAS TEBU UNTUK MENINGKATKAN KUAT TEKAN PADA MORTAR GEOPOLYMER BERBASIS FLY ASH - Handika, M Ghali; Firdaus, Firdaus (Ensiklopedia of Journal, 2024)
The aim of this research was to determine the effect of substitution of bagasse ash for fly ash on the compressive strength of geopolymer concrete mortar with variations in eggshell ash mixtures of 0%, 5%, 10% and 15% at ages 7, 14 and 28 days.  This research includes testing the compressive strength of geopolymer mortar. From the results of the compressive strength of the mortar in laboratory tests, the compressive strength of the mortar increased after adding bagasse ash at a percentage of 5% and 10% and had an optimum compressive strength with a variation of 15%. The increase in the compressive strength of the mortar is due to the fact that bagasse ash has a fairly high silica content. The silica content in the concrete mixture is needed in the binding reaction of the existing compounds. Based on the test results, it was found that the compressive strength of mortar variations of 5%, 10% and 15% was 11.87 MPa at 28 days, so the compressive strength of this mortar was used as a reference for the compressive strength of mortar with the addition of bagasse ash which has optimum compressive strength. Keywords: Geopolymer mortar, bagasse ash, and compressive strength